2017
DOI: 10.1016/j.mechatronics.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Saturation based nonlinear depth and yaw control of underwater vehicles with stability analysis and real-time experiments

Abstract: International audienceThis paper deals with two nonlinear controllers based on saturation functions with varying parameters, for set-point regulation and trajectory tracking on an Underwater Vehicle. The proposed controllers combine the advantages of robust control and easy tuning in real applications. The stability of the closed-loop system with the proposed nonlinear controllers is proven by Lyapunov arguments. Experimental results for the trajectory tracking control in 2 degrees of freedom, these are the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 14 publications
2
43
0
1
Order By: Relevance
“…In practical applications, it can be observed that a standard PID control design can be improved by bounding its signal [15]. Consequently, several nonlinear bounded PID controllers have been proposed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In practical applications, it can be observed that a standard PID control design can be improved by bounding its signal [15]. Consequently, several nonlinear bounded PID controllers have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results show that the VSPID with AW reduces the overshoot as well as the settling time compared to the nominal VSPID. Finally, inspired by the works of [19] and [20], a nonlinear PD and PD+ controllers for trajectory tracking on depth and yaw dynamics of an AUV has been proposed in [15]. In this work, the authors introduced a whole set of nonlinear functions to improve the PD controller.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nonlinear feedback gains concept of NLPID has been applied later to different experimental platforms showing better control performance compared to the static feedback gains theory. One can mention: a NLPID controller applied to a parallel robot (Su, Duan, & Zheng, 2004), an Augmented NLPD controller applied to a serial manipulator (Kelly & Carelli, 1996), a parallel robot (Shang, Cong, Li, & Jiang, 2009), and an underwater vehicle (Campos, Chemori, Creuze, Torres, & Lozano, 2017), and an extended Desired Compensation Adaptation Law (DCAL) applied to a parallel robot (Bennehar, Chemori, & Pierrot, 2016).…”
Section: Introductionmentioning
confidence: 99%